Fast feed - Glover, D. (Track Coach, 2019)
Just how fast are the fastest sprinters? John Shepherd looks at IAAF stats from the world indoors. Adapted with permission from Athletics Weekly, March 28, 2019. At last year`s World Indoor Championships in Birmingham the IAAF followed up its biomechanics analy-ses from the 2017 World Champion-ships in London with further event by event reports. Here we take a look at the one produced for the 60m which was won by Christian Coleman in 6.37.Coleman`s time was set just a couple of weeks after he broke the world 60m record by five hundredths of a second and it took down the 20-year-old championship record. The data was produced by Carnegie School of Sport, Leeds Beckett University and the IAAF. You can download all event reports from the 2018 World Indoor Championships and the 2017 World Championships by going to the IAAF website.